Bridging Gaps in ESP: A Need Analysis for AI-Integrated Food and Beverage Service Module (Scripta : English Department Journal, 2026)
This study investigates the needs underlying the development of an English for Specific Purposes (ESP) module for Food and Beverage Service (FBS) integrated with AI-generated listening audio in vocational education. Although ESP materials are expected to reflect workplace communication demands, preliminary observations reveal a mismatch between instructional content and industry-relevant language use, particularly in listening competence. This study employed a mixed-method approach, collecting data through document analysis of lesson plans and syllabi, questionnaires with closed and open-ended items completed by vocational students, and interviews with instructors and industry practitioners. The analysis focuses on learners’ necessities, lacks, and wants. The findings indicate that students require authentic, workplace-oriented materials, especially those supporting listening and speaking in real hospitality contexts. However, significant gaps persist, including limited exposure to authentic listening input, insufficient practice opportunities, and low confidence in interacting with international guests. Students also prefer structured, flexible, and context-specific materials incorporating dialogue-based audio and diverse accents. These findings highlight a mismatch between learners’ needs and existing instructional practices. The study concludes that AI-generated audio offers a promising solution by providing customizable and authentic listening input, although its effectiveness depends on alignment with pedagogical principles and learner needs.